2019
DOI: 10.1002/jper.18-0415
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mandibular third molar surgical extraction on the periodontal status of adjacent second molars

Abstract: Background The periodontal health distal of second molars (M2) is often compromised because of third molar (M3) impactions. The aim of this study was to evaluate healing and periodontal status of mandibular M2 after M3 surgical extraction. Methods Eighty‐nine consecutive patients with 89 asymptomatic M3 who needed surgical extraction of one fully‐ or semi‐impacted M3 entered this study. Clinical measurements, probing pocket depth (PPD), clinical attachment level (CAL), plaque index (PI), gingival index (GI), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 39 publications
(134 reference statements)
2
45
3
5
Order By: Relevance
“…We suspect that when deep pockets have been colonized with a mass of bacteria, it is difficult to completely eliminate these microorganisms using only routine maintenance methods, and more comprehensive and complex treatments (e.g., subgingival scaling) may be needed. Recently, a study on subgingival scaling before mandibular I‐M3 extraction reported that a PD ≥4 mm was still present in 26.4% of M2s after adjacent I‐M3 removal (Passarelli et al, 2019). These results demonstrate that once substantial periodontal destruction of M2s occurs, it is difficult to completely recover in response to M3 removal, even with the aid of certain periodontal therapies.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that when deep pockets have been colonized with a mass of bacteria, it is difficult to completely eliminate these microorganisms using only routine maintenance methods, and more comprehensive and complex treatments (e.g., subgingival scaling) may be needed. Recently, a study on subgingival scaling before mandibular I‐M3 extraction reported that a PD ≥4 mm was still present in 26.4% of M2s after adjacent I‐M3 removal (Passarelli et al, 2019). These results demonstrate that once substantial periodontal destruction of M2s occurs, it is difficult to completely recover in response to M3 removal, even with the aid of certain periodontal therapies.…”
Section: Discussionmentioning
confidence: 99%
“…There are too many factors affect a M2's life span [6,19], that's why to date there is no direct evidence revealing the relationship of M2 loss with their neighboring M3s. It's generally believed that the negative effect of M3s mainly occurred in the distal M2s [9,13,20], thus the prevalence of M2 loss due to diseases in the distal surface may reflect the influence of M3s on the adjacent M2s. On the basis of this assumption, we compared the incidence of distal diseases in extracted M2s adjacent to different status of M3s.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of M3s is generally believed to increase the residual periodontal pockets and caries risks of M2s [24,26,28], the decision on preventive extraction of asymptomatic M3s is hard for dentists and patients [17,29]. Even in most studies, the preventive extraction of M3s can be benefit for the health of neighboring M2s [11,13,14], in many clinical situations, asymptomatic M3s are indeed more likely retained until irreversible damages happen [15,16]. Such evidence were also found in this study (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as in total extraction, the prognosis of a DBD continues to challenge clinicians [4]. Most studies have claimed that a DBD of the M2M remains unchanged or improves [5][6][7] but several other studies have suggested that this condition worsens after M3M surgery [8]. The reason for this difference could be because of an unsatisfactory design of the clinical study [9,10] and/or limitations in periodontal-probing factors (pocket depth and attachment loss).…”
mentioning
confidence: 99%